Implementation of MIS (Management InformationSystem) to Improve Efficiency and Security of Interbank transactions Using BCA Mobile (Case Study at Bank BCA Tbk) - Handoko, Melyani; Yulianto, Andri Rizko; Jatinurcahyo, R.; Subariyanti, Herudini; Nikmah, Wasilatun; Adawia, Popon Rabia; Yulianto; Armaniah, Henny (Journal of Management and Informatics, 2025)
The rapid advancement of digital technology has revolutionized the financial services industry, compelling banks to adopt more efficient and secure digital platforms. This study explores the implementation of a Management Information System (MIS) to enhance the efficiency and security of interbank transactions through the BCA Mobile application, a leading digital banking solution provided by PT Bank Central Asia (BCA). The research employs a case study approach and gathers primary data from 30 respondents who are active users of BCA Mobile. Using SPSS for validity testing, the results indicate that the efficiency variable (X1) has a strong and significant positive correlation with improved transaction performance, while the security variable (X2) also contributes positively, albeit to a lesser degree. The findings suggest that an integrated MIS—featuring rapid data access, process automation, and biometric authentication—can substantially enhance operational reliability and customer trust. Moreover, the prototype development model used in this study supports user-centered design iterations to optimize usability and system functionality. The research contributes to digital banking literature by demonstrating how a tailored MIS can support financial inclusion, customer satisfaction, and strategic agility in Indonesia’s competitive banking sector. It also offers practical implications for banks seeking to minimize operational risks and improve service quality through system innovation. This study underscores the significance of continual MIS enhancements to sustain customer confidence and address evolving cybersecurity threats in the digital era.